2022
DOI: 10.3390/biomedicines10020476
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy Combined with Platelet-Rich Plasma during Preventive and Therapeutic Stages of Intrauterine Adhesion in a Rat Model

Abstract: Intrauterine adhesion (IUA) is caused by artificial endometrial damage during intrauterine cavity surgery. The typical phenotype involves loss of spontaneous endometrium recovery and angiogenesis. Undesirable symptoms include abnormal menstruation and infertility; therefore, prevention and early treatment of IUA remain crucial issues. Extracorporeal shockwave therapy (ESWT) major proposed therapeutic mechanisms include neovascularization, tissue regeneration, and fibrosis. We examined the effects of ESWT and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 98 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…19 Several studies have reported that serum IL-6 levels are generally higher in IUA model mice than in normal mice. 20,21 Another cytokine connected with the immunological response is IL-17A. Its elevated levels can trigger an inflammatory response and exacerbate fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Several studies have reported that serum IL-6 levels are generally higher in IUA model mice than in normal mice. 20,21 Another cytokine connected with the immunological response is IL-17A. Its elevated levels can trigger an inflammatory response and exacerbate fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐6, a proinflammatory cytokine secreted by T cells and macrophages, stimulates the immune response and promotes fibrosis by regulating TGFβ signaling and stimulating fibroblast proliferation as well as collagen production 19 . Several studies have reported that serum IL‐6 levels are generally higher in IUA model mice than in normal mice 20,21 . Another cytokine connected with the immunological response is IL‐17A.…”
Section: Discussionmentioning
confidence: 99%
“…Being the implant sites of blastocytes, endometrium undoubtedly plays a crucial role in female pregnancy. Asherman’s syndrome, also called intrauterine adhesion (IUA), is characterized by poor glandular epithelial growth and vascular development from scarring, and fibrosis primarily caused by artificial trauma, repeated endometritis, and infection [ 59 , 73 , 74 ]. Endometrial fibrosis causes a loss of regeneration competence in functional endometrium, which eventually leads to secondary infertility, the most common type of infertility worldwide [ 60 , 75 ].…”
Section: Molecular Mechanisms Of Exosomesmentioning
confidence: 99%
“…G-CSF has been used in some studies to demonstrate contradictory efficacy. 122 According to the findings of Zadehmodarres’ pilot study, platelet-rich plasma promotes endometrial growth in patients with thin endometrium and pregnancy in infertile patients. 123 Dogras et al.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that extracorporeal shock wave therapy can improve its efficacy by collaborating with platelet-rich plasma. 122 These measures can be used in conjunction with uterine tissue engineering, but severe injuries such as partial or subtotal hysterectomy still necessitate more sophisticated tissue engineering systems.…”
Section: Introductionmentioning
confidence: 99%